Dyslexia in the aspect of Malay language spelling - Wan Mohammad, Wan Muna Ruzanna; Subramaniam, Vijayaletchumy; Abdul Aziz, Adi Yasran; Abd Rahim, Normaliza (Center for Promoting Ideas, 2011)
This study was focusing on dyslexics who have problems with spellings from the aspects of learning bahasa Melayu. The purpose of the study was to see the errors made by the dyslexics according to the Levinson Theory 1994 especially from the angle of spelling errors. The study was conducted at Taman Maluri Secondary School, Cheras Kuala Lumpur. Interview and reading and spelling test were used in the study. The reading and spelling test was done by using the dyslexia exercise books and short stories as the instruments. This was done to determine the spelling errors listed by Levinson in his theory. The findings of the study said that dyslexics have difficulties in identifying phonemes. The exchanging of letters occurs very often during the spelling process. Among the letters that are often mixed-up by the students are ‘b-d’, ‘u-n’, ‘m-w’, ‘g-q’, ‘p-q’, and ‘b-p’. Dyslexics are gifted with many huge talents. Therefore, parents, teachers and society should give their best support to convince the dyslexics to continue striving for excellence in their life and study. Among the prominent dyslexics are Orlando Bloom, Jacky Chan, the Mc Dreamy, Patrick Dempsey, Whoopy Golberg, Albert Einstein, and Tom Cruise. For this study the researcher aims to see the correct techniques and process of the teaching and learning for these dyslexics.